(untitled) (Research, Society and Development, 2022)
This is a work on consumer behavior, especially those who consume second-hand products, in the fashion segment, since thrift stores, in recent years, have significantly increased their role in the fashion market, with a proposal , among other factors, aimed at environmental awareness. In Brazil, following a global trend, SERASA (2019) points out that 3 people out of every ten respondents in its database claim to have consumed a used product in 2019, by retail stores, what reinforces the importance of how to know this better. Consumer and relate their behavior to an environmentally conscious attitude. The objective of the research is to measure the environmental awareness of consumers in a particular second-hand store, or thrift store, through the NEP scale, an instrument validated in the field of academic research on environmental awareness, which is presented in a form. With this discussion we seek to answer the following question: Is it possible to say that there is environmental awareness on the part of thrift shop consumers? It is intended, through this research, to obtain evidence of environmental awareness of the patrons of this type of second hand store, since one of the aspects that drive the consumption of used products, pointed out in the scientific literature, is the critical and environmentally conscious, or socio-environmental, approach. The methodology used the NEP questionnaire, with minor adjustments to the study, using a Likert-type scale (1-5), through data collection approaches using Google forms, with data analysis using the SPSS software.